Redox-Neutral 1,2-Dicarbofunctionalization of Buta-1,3-diene by Merging Decatungstate and Chromium Catalysis - Ding, Du; Wang, Pu-Sheng (Synthesis, 2024)
Homoallylic alcohol is a significantly useful intermediate in organic synthesis. Here we establish a three-component Nozaki–Hiyama–Kishi (NHK) type reaction of buta-1,3-diene, aldehydes, and aliphatic C–H partners by merging decatungstate and chromium catalysis, enabling a modular, redox-neutral, and atom-economic strategy to access a diverse range of homoallylic alcohols.
Keywords: photocatalysis; C–H activation; chromium catalysis; multicomponent reaction; buta-1,3-diene; homoallylic alcohols